2007
DOI: 10.1200/jco.2007.12.3026
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Efficacy and Safety of Bevacizumab in Combination With Chemotherapy or Erlotinib Compared With Chemotherapy Alone for Treatment of Recurrent or Refractory Non–Small-Cell Lung Cancer

Abstract: Results for PFS and overall survival favor combination of bevacizumab with either chemotherapy or erlotinib over chemotherapy alone in the second-line setting. No unexpected safety signals were noted. The rate of fatal pulmonary hemorrhage was consistent with previous bevacizumab trials. The toxicity profile of the bevacizumab-erlotinib combination is favorable compared with either chemotherapy-containing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
245
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(250 citation statements)
references
References 16 publications
2
245
0
3
Order By: Relevance
“…This was recently confirmed by Manegold et al (2008). Moreover, a phase I/II trial combining the epidermal growth factor receptor (EGFR) inhibitor erlotinib or chemotherapy with bevacizumab resulted in higher response rates and longer median progression-free survival (PFS) in both bevacizumab containing arms (Herbst et al, 2007).…”
mentioning
confidence: 56%
“…This was recently confirmed by Manegold et al (2008). Moreover, a phase I/II trial combining the epidermal growth factor receptor (EGFR) inhibitor erlotinib or chemotherapy with bevacizumab resulted in higher response rates and longer median progression-free survival (PFS) in both bevacizumab containing arms (Herbst et al, 2007).…”
mentioning
confidence: 56%
“…In that trial, 28% of patients discontinued treatment in the bevacizumab-chemotherapy arm as a result of adverse effects, versus 24% of patients treated with only chemotherapy. The progressionfree survival (PFS) intervals were similar in the bevacizumaberlotinib and bevacizumab-chemotherapy arms (4.4 months versus 4.8 months) [21].…”
Section: Other Investigational Combination Therapiesmentioning
confidence: 89%
“…Unlike EGFR-tyrosine kinase inhibitors, antiangiogenic agents combined with conventional chemotherapy have demonstrated clinical benefit in NSCLC (Herbst et al, 2007), and recent studies have demonstrated the safety of enzastaurin combination with cytotoxic drugs (Rademaker-Lakhai et al, 2007), including pemetrexed (Hanauske et al, 2006). Furthermore, our findings are novel because they show that the synergistic interaction seems to be mediated by several mechanisms, summarised in Figure 6, which enhanced the sensitivity to pemetrexed and should be used as predictive biomarkers for the future clinical development of enzastaurin-pemetrexed combination.…”
Section: Discussionmentioning
confidence: 99%